Doing design ethnography - Crabtree,Andrew; Rouncefield,Mark; Tolmie, Peter
Ethnography is now a fundamental feature of design practice, taught in universities worldwide and practiced widely in commerce. Despite its rise to prominence a great many competing perspectives exist and there are few practical texts to support the development of competence. Doing Design Ethnography elaborates the ethnomethodological perspective on ethnography, a distinctive approach that provides canonical 'studies of work' in and for design. It provides an extensive treatment of the approach, with a particular slant on providing a pedagogical text that will support the development